Phenserine efficacy in Alzheimer's disease - Winblad, Bengt; Giacobini, Ezio; Frölich, Lutz; Friedhoff, Lawrence T.; Bruinsma, Gosse; Becker, Robert E.; Greig, Nigel H. (Journal of Alzheimer's disease, 2010)
To gather preliminary evidence in Alzheimer's disease (AD) for the efficacy of phenserine, a non-competitive acetylcholinesterase inhibitor that has independent modulatory effects on amyloid-β generation, a 12-week comparison of patients receiving ph